2013
DOI: 10.4081/jphia.2013.e10
|View full text |Cite
|
Sign up to set email alerts
|

Socio cultural and geographical determinants of child immunisation in Borno State, Nigeria

Abstract: Immunisation has been an important strategy for disease prevention globally. Despite proven successes in other settings, child immunisation has continued to be problematic in developing countries including Nigeria. In addressing the problems, policy in Nigeria is largely directed at overcoming socio cultural issues surrounding parents’ rejection of vaccines. However, determinants of immunisation have geographical implications as well. A cross sectional survey was used to select 484 mothers/caregivers through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“… Factor Frequency Note Reference Individual factors Maternal factors Maternal literacy and education 22 High maternal education consistently associated with higher vaccination rates, although one national study found that education level was not significant when adjusted for literacy [32] . [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] Maternal care (health facility birth) 12 Giving birth in a health facility was significantly associated with vaccination, particularly for birth doses. However, delivery on weekends or outside routine vaccination days, and prematurity or low birth weight, were reasons for delayed or missed birth dose vaccinations [54] .…”
Section: Resultsmentioning
confidence: 99%
“… Factor Frequency Note Reference Individual factors Maternal factors Maternal literacy and education 22 High maternal education consistently associated with higher vaccination rates, although one national study found that education level was not significant when adjusted for literacy [32] . [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] Maternal care (health facility birth) 12 Giving birth in a health facility was significantly associated with vaccination, particularly for birth doses. However, delivery on weekends or outside routine vaccination days, and prematurity or low birth weight, were reasons for delayed or missed birth dose vaccinations [54] .…”
Section: Resultsmentioning
confidence: 99%
“…[15][16][17][18] Travel time to a health post has been reported as one of the community-level determinants for vaccination coverage in many studies. 12,19 A study in Nepal found that travel time to the nearest health center was negatively associated with child immunization, 20 whereas a study in Bangladesh found that distance to the health facility less than 1 kilometer was a significant predictor of complete immunization coverage. 21 However, Bangladesh has several tiers of public health facilities that operate in tandem with private and nonprofit services.…”
Section: Introductionmentioning
confidence: 99%
“…6 Previous studies linking individual- or household-level sociodemographic factors to differences in vaccination coverage have considered birth order of the child, gender, and parental factors such as education, household wealth status, mother’s intention of pregnancy for the indexed child, among other factors. 11-13 For example, it is widely presumed that those who are well educated and of greater socioeconomic status are more able to access necessary transport to get to a vaccination center or health facility than those less educated or wealthy. Moreover, mothers with higher education are more likely to know how to protect their children against disease and may participate well in public health programs.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Although studies on health care and health outcomes in Africa are not that limited as they were almost 20 years ago [40], a weakness in most of them is that they do not take people's perception of access into account. One exception is [41], who combined physical distance to the nearest immunization centre, with mothers' perceptions of distance as determinants of child immunization in Nigeria, where the perception of distance turned out to be a more robust determinant than actual distance. This highlights the need to combine people's perceptions of barriers to health care with more objective measures of accessibility to identify causes for poor access.…”
Section: The Added Value Of Our Approachmentioning
confidence: 99%